2021
DOI: 10.35313/ijatr.v2i1.43
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Implementation of Fan Chips as Cooling for Milling Process on Aluminum Alloy 5086 to Increase Tool Life

Abstract: In the metal machining process, especially in the milling process, the parameters that affect the quality milling process results are cooling media because it affects the tool life used. This paper aims to determine the performance of using fan chips as the coolant in the dry milling process area. The method used is the computational fluid dynamic (CFD) method and the experimental milling process on a workpiece made from aluminum alloy 5086. In experimental testing using a variation of the milling machine spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…The temperature decrements are almost halves (around 73 to 113°C, or around ~40%) for the finishing process and more than half (around 47 -57%) for roughing process. This evidence showed that forced convection from the MQL Chip fan made a huge impact on the cooling processes [30].…”
Section: Experimental Temperature Datamentioning
confidence: 92%
“…The temperature decrements are almost halves (around 73 to 113°C, or around ~40%) for the finishing process and more than half (around 47 -57%) for roughing process. This evidence showed that forced convection from the MQL Chip fan made a huge impact on the cooling processes [30].…”
Section: Experimental Temperature Datamentioning
confidence: 92%
“…Pada gambar 3 Menunjukkan hasil simulasi CFD bilah model 2 dengan jumlah 3 bilah fan chip portable untuk pendinginan proses pengeboran logam, dimana ditunjukkan pada hasil simulasi kecepatan dan temperature udara, dimana nilai maksimimum temperature udara sebesar 30,19 O C dan nilai minimum temperature udara sebesar 29,87 O C, minimum temperatur sebagai pendingin untuk udara dingin fan chip yang ditiupkan pada proses pendinginan tool [15]. Pada tabel 3 dan tabel 4, menunjukkan hasil yang berbeda dari setiap desain fan chip.…”
Section: Gambar 3 Cfd Jumlah Bilahunclassified